2018
DOI: 10.1002/lpor.201800016
|View full text |Cite
|
Sign up to set email alerts
|

All‐Optical Phosphorene Phase Modulator with Enhanced Stability Under Ambient Conditions

Abstract: All‐optical modulators, wherein signal light can be manipulated by another controlling light, have recently emerged as a promising perspective in all‐optical communications, interconnects and signal processing. Herein, by taking advantage of the strong light‐matter interaction and thickness‐dependent direct energy bandgap in few‐layer phosphorene, an all‐fiber all‐optical modulator based on a Mach–Zehnder interferometer comprising few‐layer fluorinated phosphorene‐deposited microfiber has been devised and furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
92
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 163 publications
(92 citation statements)
references
References 64 publications
(106 reference statements)
0
92
0
Order By: Relevance
“…As for optical modulation, an indispensable technology for modern optical communication, controlling optical properties of a material by changing its refractive index is a widely adopted pathway . The refractive index of a material, however, is temperature dependent, which implies a way for optical modulation mediated by thermal control.…”
Section: Comparison Of Different 2d Materials‐based Similar Devicesmentioning
confidence: 99%
“…As for optical modulation, an indispensable technology for modern optical communication, controlling optical properties of a material by changing its refractive index is a widely adopted pathway . The refractive index of a material, however, is temperature dependent, which implies a way for optical modulation mediated by thermal control.…”
Section: Comparison Of Different 2d Materials‐based Similar Devicesmentioning
confidence: 99%
“…Meanwhile, for future optical networks, all‐optical devices have become the focus because of their easy integration, low loss, and good compatibility with optical fiber systems. The modulator accounts for a significant component in the application of optical connections . The all‐optical modulator with a materials‐based device has good prospects in optical communications and optical information processing fields.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, all‐optical modulators with WS 2 ‐ and BP‐based devices were published. Because of the thermal effects of 2D materials, the maximum obtained phase shifts were 6π and 8π, and the rise time constants were 7.3 and 2.5 ms …”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Fiber all-optical light control utilizes mature ber technologies and allows alloptical devices to be compatible with current ber communication systems. Therefore, ber all-optical light control has attracted widespread research interests and many of the latest results have reported all-optical modulators, [8][9][10][11][12][13][14][15][16][17] phase shiers, 12,14,[17][18][19] logic gates, 12,14,20 and switches. 2,[5][6][7]15,18,19,[21][22][23] Meanwhile, LDMs have been a research hotspot because of their plentiful photonic and optoelectronic properties including graphene, 9,[24][25][26][27] graphene oxide, 28,29 carbon nanotubes (CNTs), [30][31][32] transition metal dichalcogenides (TMDs), [33][34][35] topological insulators (TIs), [36]…”
Section: Introductionmentioning
confidence: 99%
“…Many all-optical devices based on these two effects have been reported. [11][12][13][14]16,[18][19][20]62,[65][66][67][68] Therefore, it is very important to build up a complete view on the principle and performance of these devices.…”
Section: Introductionmentioning
confidence: 99%